Outbreak Of Jaundice In Rural School Children: An Epidemiological Investigation - Mohite, RV; Kumbhar, SM; Tondare, MB; Ganganhali, P; Salunkhe, LR (Asian Journal of Medical Sciences, 2013)
Background: Viral hepatitis is a major public health problem in India and epidemiology of viral hepatitis is going to changing as outbreaks of hepatitis A are being reported with increased frequency, in the pediatric age group as well. Objective: To study the time, place, and person distribution of hepatitis A infection in rural school population & to find the source of infection in the study area. Methodology: Community based survey was conducted among the school population of village Kalawade district Satara of state Maharashtra during July-August 2011 by interview and clinical examination utilizing pre-designed semi-structured proforma. Data collected by investigation team was compiled and presented into frequency, percentage & chi-square test was applied to know the statistical association. Results: Out of 400 school children, 32 suffered from Hepatitis A viral infection with overall attack rate 8% involving 25 males & 7 females showed statistical significant association (p < 0.05). Index case was detected on 20th July 2011 while maximum no. of cases i.e. 11 cases were detected during 3rd week of outbreak with a median incubation period 21 days. Majority of patients, 96.8% & 81.2% were presented with dark yellow colored urine and yellowish discoloration of sclera. Out of 32 patients, 68.5% cases were from private high school with water supply from bore well while 31.5% cases from anganwadies & primary school with a water supply from gram panchayat well. However, water supply source to private high school was found contaminated. Conclusion: An outbreak of Hepatitis A reported in school children mainly due to consumption of contaminated bore well water. Asian Journal of Medical Science, Volume-3 No-3 (2012), Page -20-26 DOI: http://dx.doi.org/10.3126/ajms.v3i3.7743